ИСТОЧНИКИ МИГРАЦИОННОГО ПРАВА РЕСПУБЛИКИ КАЗАХСТАН (Journal of actual problems of jurisprudence, 2019)
In a modern state regulation of the flow of population movement is an important element of the organization of society andmaintain order. This activity is essential to national security. Migration is one of the sources of the population in different countries.